2013
DOI: 10.1111/ijfs.12419
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, functional properties and microstructural characteristics of three kabuli chickpea (Cicer arietinum L.) as affected by different cooking methods

Abstract: Summary Chickpea is an important food legume and is a major ingredient in many human diets. Chemical composition, physical parameters, functional properties and microstructural characteristics of three kabuli chickpea cultivars and the effects of three cooking methods were investigated. Carbohydrate and protein were two major components in all seeds. Cooking increased fibre, total carbohydrate and total and resistant starch contents, but decreased ash content. Protein and oil levels of the cooked samples eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 22 publications
4
45
1
Order By: Relevance
“…These authors also found increased soluble fiber in extruded peas. Boiling, pressure cooking, and microwaving processing caused an increased fiber content in chickpeas (El-Adawy 2002; Xu et al 2014). No change in dietary fiber was observed in extruded kidney beans or peas (Alonso et al 2001).…”
Section: Carbohydrate Content and Composition Of Pulse Cropsmentioning
confidence: 99%
“…These authors also found increased soluble fiber in extruded peas. Boiling, pressure cooking, and microwaving processing caused an increased fiber content in chickpeas (El-Adawy 2002; Xu et al 2014). No change in dietary fiber was observed in extruded kidney beans or peas (Alonso et al 2001).…”
Section: Carbohydrate Content and Composition Of Pulse Cropsmentioning
confidence: 99%
“…Chickpea is a protein (19-29 g/100 g) and carbohydrates (60-65 g/100 g) rich legume (Boye et al 2010) and it is a source of B complex vitamins and minerals (Seena and Sridhar 2005). These nutritional properties can be even improved using processing methods like germination, cooking or toasted that increase the protein digestibility (Almeida Costa et al 2006;Xu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…All results were analyzed with SAS version 9.3 statistical software (SAS Institute Inc., Cary, NC). ANOVA with Duncan's multiple range test was used to evaluate the statistical significance in composition and properties with significant level of probability (P) B 0.05 as described by Xu et al [27].…”
Section: Resultsmentioning
confidence: 99%
“…Morphologies of freeze-dried raw and cooked edamame flours were visualized and evaluated using a SU-70 scanning electron microscope (Hitachi, Japan) as described by Xu et al [27]. A thin layer of each sample was mounted on an aluminum specimen holder using double-sided tape, and coated with gold palladium to a thickness of 30 nm.…”
Section: Microstructural Characteristicsmentioning
confidence: 99%